Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1101/2022.06.13.22276339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of hydrometeorological and other factors on SARS-CoV-2 reproduction number in three contiguous countries of Tropical Andean South America: a spatiotemporally disaggregated time series analysis

Abstract: Background: The COVID-19 pandemic has caused societal disruption globally and South America has been hit harder than other lower-income regions. This study modeled effects of 6 weather variables on district-level SARS-CoV-2 reproduction numbers (Rt) in three contiguous countries of Tropical Andean South America (Colombia, Ecuador, and Peru), adjusting for environmental, policy, healthcare infrastructural and other factors. Methods: Daily time-series data on SARS-CoV-2 infections were sourced from health author… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Merow and Urban pointed out a temporary decline in SARS-CoV-2 infection in the summer, whereas, in the autumn, the COVID-19 cases rose and reached the maximum in the winter. A study conducted in Brazil showed the seasonality of COVID-19 transmission [27]. Studies on respiratory diseases have demonstrated that seasonal rotation influences the rise of respiratory virus outbreaks [26].…”
Section: Sars-cov-2 and Environmental/climatic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Merow and Urban pointed out a temporary decline in SARS-CoV-2 infection in the summer, whereas, in the autumn, the COVID-19 cases rose and reached the maximum in the winter. A study conducted in Brazil showed the seasonality of COVID-19 transmission [27]. Studies on respiratory diseases have demonstrated that seasonal rotation influences the rise of respiratory virus outbreaks [26].…”
Section: Sars-cov-2 and Environmental/climatic Factorsmentioning
confidence: 99%
“…Merow and Urban pointed out a temporary decline in SARS-CoV-2 infection in the summer, whereas, in the autumn, the COVID-19 cases rose and reached the maximum in the winter. A study conducted in Brazil showed the seasonality of COVID-19 transmission [27].…”
Section: Sars-cov-2 and Environmental/climatic Factorsmentioning
confidence: 99%